The Influence of ROE, NPF, FDR, BOPO and Bank Size on Capital Buffer in Sharia Commercial Banks for the 2016-2022 Period - Sahrianti Ritonga, Alpi; Falahuddin, Falahuddin (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
This research aims to examine the influence of ROE, NPF, FDR, BOPO and Bank Size on Capital Buffer in Islamic commercial banks for the 2016-2022 period. The population in this study consisted of 14 banks. The sampling technique used purposive sampling to obtain 7 banking samples with 49 observations. This research is quantitative research using secondary data used in this research which comes from the annual financial reports of each bank via the official banking website which is analyzed using panel data regression analysis. The results of this research show that the Return on Equity (ROE) variable has a positive and insignificant effect on the Capital Buffer, the Non Performing Finance (NPF) variable has a negative and significant effect on the Capital Buffer, the Financing to Deposit Ratio (FDR) variable has a positive and insignificant effect on the Capital Buffer, the Operational Costs Operational Income (BOPO) variable has a positive and insignificant effect on the Capital Buffer, the Bank Size variable has a positive and insignificant effect on the Capital Buffer.